La testimonianza letteraria come fonte storica: il caso della letteratura dei gulag - Ljuba Jurgenson (Lea, 2016)
The tension or even antagonism between testimony and historical writing has nourished epistemological studies at the crossroads of several disciplines (philosophy, sociology, literature). However, the specificity of the testimonies of the Gulag is rarely taken into account by this analysis. This article proposes some paths of reflection on the epistemological perspectives of the dialogue between the historian and the authors of testimonies.